2011
DOI: 10.1128/aac.00478-11
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Efficacy of Dicationic Compounds and Mefloquine Enantiomers against Echinococcus multilocularis Metacestodes

Abstract: The current chemotherapy of alveolar echinococcosis (AE) is based on benzimidazoles such as albendazole and has been shown to be parasitostatic rather than parasiticidal, requiring lifelong duration. Thus, new and more efficient treatment options are urgently needed. By employing a recently validated assay based on the release of functional phosphoglucose isomerase (PGI) from dying parasites, the activities of 26 dicationic compounds and of the (؉)-and (؊)-erythro-enantiomers of mefloquine were investigated. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 49 publications
3
24
0
1
Order By: Relevance
“…2012), Besnoitia besnoiti (Cortes et al . 2011) and Echinococcus multilocularis (Stadelmann et al . 2011).…”
Section: Design and Synthesisunclassified
“…2012), Besnoitia besnoiti (Cortes et al . 2011) and Echinococcus multilocularis (Stadelmann et al . 2011).…”
Section: Design and Synthesisunclassified
“…The in vivo effects of DB1127 were investigated and compared to those of standard oral albendazole treatments. Two experiments were performed, one assessing the intraperitoneal (21) and one the oral (30) delivery route. DB1127 was prepared as a stock solution in DMSO and diluted 1,000 times with 1% carboxymethyl cellulose (CMC) in saline solution.…”
Section: Methodsmentioning
confidence: 99%
“…PGI is abundant in metacestode vesicle fluid and released into the metacestode culture supernatant by dying parasites, while intact, viable metacestodes do not release this enzyme (26). Recently, we demonstrated that DB1127, a dicationic thiophene derivative (di-Naryl-diguanidino compound), triggered the release of high levels of PGI activity from metacestodes in a dose-dependent manner, was substantially active at concentrations as low as 1 M, and induced structural damage upon E. multilocularis metacestodes (21).…”
Section: T He Disease Alveolar Echinococcosis (Ae) Is Caused By Infecmentioning
confidence: 99%
See 1 more Smart Citation
“…All but one of the drugs tested, imatinib, have been proposed to have anticestode activity in other in vitro or in vivo assays (13,(19)(20)(21). Nitazoxanide and artesunate showed effects on the release of both enzymes, which reinforces the utility of these assays for drug screening.…”
Section: Discussionmentioning
confidence: 78%